Jurusan Manajemen Fakultas Ekonomi Universitas Mataram JL. Majapahit No.62, Mataram, Nusa Tenggara Barat, 83125 - Putra, I Nyoman Nugraha Ardana (UNIVERSITY OF MERDEKA MALANG, 2012)
This study aimed to examine and to explain the influence of managerial ownership and credit risks towardagency costs and performance. The study was also intended to enrich the empirical evidence of agency theory infinancial management of the Microfinance Institutions (MFIs), especially managerial ownership of society creditbank (BPR) in West Nusa Tenggara province. Secondary data used was derived from financial statements andprimary data obtained from interviews with the director of bank samples. Partial Least Square technique Programs(PLS) was applied to test the research model in term of variables relationship structure in quantitativemethods The results. The results showed that managerial ownership had a positive influence on credit risks andalso had a positive impact on agency costs. In addition to managerial ownership and agency costs, this researchfound that there was a negative effect of company performance.